Phrenic neuropathy and diaphragm dysfunction in neuralgic amyotrophy. (28th August 2018) - van Alfen, Nens; Doorduin, Jonne; van Rosmalen, Marieke H.J.; van Eijk, Jeroen J.J.; Heijdra, Yvonne; Boon, Andrea J.; Gaytant, Michael A.; van den Biggelaar, Ries J.M.; Sprooten, Roy T.M.; Wijkstra, Peter J.; Groothuis, Jan T.
Abstract : Objective: To describe the clinical phenotype and recovery of diaphragm dysfunction caused by neuralgic amyotrophy in a large cohort of patients, to improve accurate awareness of this entity, and to encourage adoption of a standardized approach for diagnosis and treatment. Methods: This observational cohort study recruited adult patients with neuralgic amyotrophy and symptoms of idiopathic phrenic neuropathy from the database of the Dutch expert center for neuralgic amyotrophy and the Dutch centers for home mechanical ventilation. Demographic and clinical information on diagnosis, symptoms, and recovery was obtained from chart review. We attempted to contact all patients for a follow-up interview. Results: Phrenic neuropathy occurs in 7.6% of patients with neuralgic amyotrophy. Unilateral diaphragmatic dysfunction and bilateral diaphragmatic dysfunction are frequently symptomatic, causing exertional dyspnea, orthopnea, disturbed sleep, and excessive fatigue. Diagnostic practices varied widely and were often not optimally targeted. The majority of patients experienced at least moderate recovery within 2 years. Conclusion: We recommend screening every patient with neuralgic amyotrophy for diaphragm dysfunction by asking about orthopnea and by performing upright and supine vital capacity screening and diaphragm ultrasound in cases of suspected phrenic neuropathy to optimize diagnosis and care.